The Effect of Divorce on Early Childhood Academic Achievement - Najla Sausan Alifa; Adilla Julia Pratama (Socrates: Journal of Education, Philosophy and Psychology, 2025)
The objectives achieved in this study describe the impact of parental divorce on student learning achievement. This study uses descriptive research. The results of the study obtained: from the results of the study it was found that the divorce of both parents had an impact on student achievement. These impacts can be negative impacts, namely decreased learning motivation, student activity during learning, withdrawn behavior, limiting social relationships and indiscipline. Children are greatly affected by divorce including their learning achievement. So that the child feels very lost in the sense of enthusiasm and lack of motivation to learn so that it can cause the child's academics to decline. In addition, the impacts such as physical and psychological children. Deep sadness can also be potential for children such as easily flared emotions, anxiety, down, and mild depression and children will also feel guilty like blaming themselves